Does Greenwashing Build Green Brand Associations? Evidence from the Indian Packaged Food Market - Khattri, Varsha; Tomar, Vivek Singh (Indian Journal of Marketing, 2024)
Purpose : Marketers engage in a tactic known as â€œgreenwashing,â€ which involves making false environmental claims in order to capitalize on consumersâ€™ desire for environmentally friendly items. This study looked at how views of â€œgreenwashingâ€ affected links between green brands and packaged foods in India. It also looked at how green concern and green skepticism function as moderators and mediators, respectively. Methodology : The study is based on a survey of 326 users of packaged food products. The questionnaire consisted of four major constructs: greenwashing perception, greenwashing skepticism, green concern, and green brand associations. The structural equation modeling (SEM) approach was applied to conclude the data. Findings : This study showed that green skepticism acts as a mediating factor between the impression of greenwashing and negative associations with green brands. It was discovered that the moderator of green concern emphasized the detrimental effect of the perception of greenwashing on affiliations with green brands. Practical Implications : The results from the study may be used by lawmakers, regulators, and packaged food marketers to frame their environmental policies and practices to reduce green skepticism by providing proof of green claims and practices. Originality : The study was distinctive in that it examined green brand linkages from the viewpoint of the notion of greenwashing. Furthermore, no research on the subject of greenwashing examined the moderating and mediating effects of green concern and green skepticism, respectively. Thus, the study addressed this research void.